IGFBP2 promotes salivary adenoid cystic carcinoma metastasis by activating the NF-κB/ZEB1 signaling pathway. (28th September 2018) - Yao, Xiaofeng; Wang, Yu; Duan, Yuansheng; Zhang, Qiang; Li, Ping; Jin, Rui; Tao, Yingjie; Zhang, Wenchao; Wang, Xudong; Jing, Chao; Zhou, Xuan
Abstract: Metastasis is a major cause of poor prognosis in patients suffered with salivary adenoid cystic carcinoma (SACC), in which many factors are implicated. In this study, we identified that IGFBP2, overexpressed in SACC, correlated positively with perineural invasion or metastasis and indicated worse outcome. Moreover, IGFBP2 overexpression could dramatically improve motility and invasion capacity of SACC cells in vitro . Mechanically, IGFBP2 enhanced expression of ZEB1 in a NF-κB (p65)-dependent manner and then promoted epithelial-mesenchymal transition (EMT) in SACC. In addition, IGFBP2 mutation in the nuclear localization signal could impede nuclear translocation of p65, lower ZEB1 expression, and abrogate the EMT process. In xenograft models, IGFBP2 overexpression promoted lung and liver metastases of SACC cells; while if nuclear IGFBP2 was reduced, the formation of metastases in lung and liver was weakened. Together, these results for the first time demonstrate that IGFBP2 plays an important role in invasion and metastasis of SACC through the NF-κB/ZEB1 signaling pathway and IGFBP2 may be a novel biomarker and target for SACC. Highlights: High level of IGFBP2 correlates positively with perineural invasion or metastasis and indicates poor prognosis in SACC. IGFBP2 promotes invasion-metastasis cascade of SACC cells in vitro and in vivo . IGFBP2 activates NF-κB (p65)/ZEB1 pathway to improve the EMT process and metastasis. Nuclear translocation of IGFBP2 is critical for its function on p65 nuclear entry, EMT process and metastasis in SACC.